An Analysis of Verbal Irony in Emma Donoghue™s Room - Harahap, Melvi Dwi Arfina; Zainuddin, Zainuddin (Universitas Negeri Medan, 2022)
The objectives of this study were to find out 1) To found out what types of verbal irony used in the novel, 2) To found out the literal meaning of the verbal irony, 3) To found out the realization of the verbal irony. The source of data was the novel, and the data were taken from the dialogue in the novel. The study conducted by using qualitative research. The data were analyzed by using Sperber and Wilson™s theory to classify the types of verbal irony. There were 13 data found and there were two types of verbal irony used in the novel spoken by the two main characters. The types were ironical understatement (92%) and ironical interjection (8%). The literal meaning and the realization of the verbal irony were known based on the context in the dialogue.